Strategies and Efforts towards the Total Synthesis of Palhinine Alkaloids - Liang, Yu-Yan (Molecules, 2020)
The palhinine family of Lycopodium alkaloids were first reported in 2010, which feature an intriguing isotwistane carbon cage and a nine-membered azonane ring. It is noteworthy that the tetracyclic 5/6/6/9 skeleton was unprecedented in Lycopodium alkaloids before their seminal discovery. Over the past decade, extensive synthetic efforts stemming from seven research groups have resulted in two racemic total syntheses to date. This review article takes the opportunity to survey these efforts and achievements so as to promote further research towards the asymmetric total synthesis of palhinine alkaloids.